Diffuse Auroral Electron and Ion Precipitation Effects on RCM‐E Comparisons With Satellite Data During the 17 March 2013 Storm. Issue 6 (20th June 2019) - Chen, Margaret W.; Lemon, Colby L.; Hecht, James; Sazykin, Stanislav; Wolf, Richard A.; Boyd, Alexander; Valek, Philip
Abstract: Effects of scattering of electrons from whistler chorus waves and of ions due to field line curvature on diffuse precipitating particle fluxes and ionospheric conductance during the large 17 March 2013 storm are examined using the self‐consistent Rice Convection Model Equilibrium (RCM‐E) model. Electrons are found to dominate the diffuse precipitating particle integrated energy flux, with large fluxes from 21:00 magnetic local time (MLT) eastward to 11:00 MLT during the storm main phase. Simulated proton and oxygen ion precipitation due to field line curvature scattering is sporadic and localized, occurring where model magnetic field lines are significantly stretched on the night side at equatorial geocentric radial distances r 0 ≳8 R E and/or at r 0 5.5 to 6.5 R E from dusk to midnight where the partial ring current field has perturbed the magnetic field. The precipitating protons likewise contribute sporadically to the storm time Hall and Pedersen conductance in localized regions whereas the precipitating electrons are the dominate storm time contributor to enhanced Hall and Pedersen conductance at auroral magnetic latitudes on the night and morning side. The RCM‐E model can reproduce general features of the Van Allen Probe/MagEIS observed trapped electron differential flux spectrograms over energies of 37 to 150 keV. The simulations with a parameterized electron loss model also reproduce reasonably well the storm time Defense Meteorological Satellite Program integrated electron energy flux at 850 km at satellite crossings from predawn to midmorning. However, model‐data agreement is not as good from dusk to premidnight where there are large uncertainties in the electron loss model. Key Points: Simulated storm time precipitating electron energy flux and average energy are significantly enhanced from premidnight to late morning Simulations reproduce reasonably well observed integrated diffuse auroral electron energy flux at 850 km from predawn to midmorning Ion precipitation due to field line curvature scattering contributes to the ionospheric conductance in localized regions